Konsep Dasar Manajemen SDM dalam Ekonomi Syariah dan Perencanaan SDM dalam Lembaga Syariah - Rizal Ancu; Asriani Asriani; Lince Bulutoding (Pusat Riset dan Inovasi Nasional, 2025)
The fundamental concept of Human Resource Management (HRM) in Islamic economics and the strategic planning of HR in Islamic institutions. In the context of a dynamic and competitive modern economy, HR management is not only aimed at achieving efficiency and productivity but must also be grounded in spiritual and ethical values. Islamic economics offers a holistic approach through Islamic principles such as tawhid (monotheism), amanah (trust), justice, and work as a form of worship. HRM in Islamic economics aims to develop a workforce that is both professional and possesses strong Islamic integrity. In addition, this also outlines strategic steps in HR planning within Islamic institutions, ranging from analyzing the need for sharia-compliant competencies to conducting compliance audits based on Islamic principles. Through this approach, Islamic institutions are expected to build sustainable and competitive organizations that contribute to the realization of a just and ethical economy.